Femtosecond-Laser-Assisted Fabrication of Radiation-Resistant Fiber Bragg Grating Sensors - Hun-Kook Choi; Young-Jun Jung; Bong-Ahn Yu; Jae-Hee Sung; Ik-Bu Sohn; Jong-Yeol Kim; Md. Shamim Ahsan (Applied Sciences, 2022)
This paper demonstrates the fabrication of radiation-resistant fiber Bragg grating (FBG) sensors using infrared femtosecond laser irradiation. FBG sensors were written inside acrylate-coated fluorine-doped single-mode specialty optical fibers. We detected the Bragg resonance at 1542 nm. By controlling the irradiation conditions, we improved the signal strength coming out from the FBG sensors. A significant reduction in the Bragg wavelength shift was detected in the fabricated FBG sensors for a radiation dose up to 105 gray, indicating excellent radiation resistance capabilities. We also characterized the temperature sensitivity of the radiation-resistant FBG sensors and detected outstanding performance.